IMPLEMENTASI KHIYAR PADA REGULASI PEMBATALAN TRANSAKSI DAN PENGEMBALIAN BARANG DI APLIKASI SHOPEE - Dani El Qori (MIYAH : Jurnal Studi Islam, 2022)
Abstract: Technological developments have changed many things in all lines of human life. including buying and selling transactions. Through internet services, the trend of online buying and selling or what is commonly called e-commerce emerged. E-commerce services offer convenience and speed in buying and selling transactions without having to meet physically. However, the advantages offered still create gaps. It is often found that there is disappointment from buyers who use e-commerce services because the goods received do not match the specifications of the goods offered. Islamic law has provided a solution to this problem through khiyar rights. The buyer can submit a cancellation of the transaction if there is a discrepancy in the goods received. In this article, the author will examine the implementation of khiyar in canceling transaction regulations on the Shopee application. This research is in the nature of literature research which makes the regulation of canceling transactions on the Shopee application the object of research. The data that has been collected will be analyzed using the theory of khiyar in fiqh. Kata kunci: khiyar, pembatalan, pengembalian, Shopee.